Use Of Scrap Tyres In Earth Retaining Structures - Loh, Wooi Chuan (2008)

(untitled)
In Malaysia, a huge quantity of scrap tyres are produced every year resulting in environmental hazards. In addition, present recycling techniques for scrap tyres consume only a very small amount of the unwanted tyres. With this in mind, this research aims to assess the technical feasibility of using whole scrap tyres as one of the elements of retaining structures. The purpose of this thesis is to demonstrate, through an experimental laboratory investigation and full scale testing, that a reinforced tyre system from scrap passenger car tyres can be used to produce engineered retaining structures for civil engineering construction. This research study is divided into three main parts: a study on the physical and mechanical properties of passenger car tyres and attachments, behaviors of reinforced scrap tyre retaining structures with cohesive material, and cost comparison of a reinforced scrap tyre system with other conventional retaining structure systems was found that the physical and mechanical properties of scrap passenger car tyres are tremendously strong. Various attachment systems were studied in terms of mechanical properties and costs. Polypropylene rope was found to be the most cost effective attachment system with comparable strength to scrap tyres. A 5m high full scale reinforced scrap tyre system been constructed using in-situ cohesive material. 2100 scrap passenger car tyres were used for the construction of a 7m long x 5m high slope. Instrumentation like pressure cells and settlement plates were installed to monitor the behavior of the system. Methods of construction and precautions during the construction stage were discussed in detail in this study. It can be concluded that the reinforced rubber tyre system is suitable for application in retaining structures. It improves the mechanical properties of the soil either anisotropically or isotropically. Cost comparison between reinforced scrap tyre systems and other retaining structure systems were studied. Reinforced scrap tyre systems can be used as alternative cost effective retaining structure system with wall heights less than 6m. This system would be one of the best recycling techniques for scrap tyres because it consumes huge amounts of unwanted tyres with minimum energy consumption.